Physical demand of wheelchair tennis match-play on hard courts and clay courts - Ponzano, M.; Gollin, M. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to define the performance model of wheelchair tennis, by means of 20 Hz GPS together with heart rate monitors, while also investigating potential surface-related differences. Hence, 12 matches performed by 12 nationally ranked wheelchair tennis players were examined. Each athlete played one match on the clay and one on the hard court according to a counterbalanced design, and the data regarding the parameters of maximum heart rate (HRmax), average heart rate (HRav), maximum speed (SPmax), average speed (SPav), maximum acceleration (ACCmax), maximum deceleration (DECmax), maximum metabolic power (MPmax), average metabolic power (MPav) and energy expenditure (EE) were analysed. The average match duration was 82 ± 16 min on clay courts (C) and 68 ± 17 min on hard courts (H) (p = .06), while the distance covered is greater, but not significant, on clay courts (C > H, +10%). The t-test did not highlight significant differences pertaining to the playing surface. The linear regression showed significant values concerning the distance covered (C: p < .0001, r2 = .82, H: r2 = .81) and the energy expenditure (C: p < .05, r2 = .5, H: r2 = .9). The playing surface does not affect the performance of competitive wheelchair tennis athletes.